PENGARUH PELAYANAN DAN PERSEPSI HARGA TERHADAP MINAT BELI MELALUI RESPON EMOSIPEMBELI PADA BRIO HONDA DI SHOWROOM HONDA ARISTA RINGROAD MEDAN - Ardina Camelin; Feronika Pasaribu; Yochi Elanda (LPPM Universitas Cipta Mandiri, 2024)
In an effort to increase sales, the Honda Brio showroom at the Honda Arista Showroom will be able to pay attention to service to buyers using various indicators, provide stable and affordable prices so as to create a good perception of price, while creating a positive emotional response to buyers, thereby increasing product sales. will be able to increase further. This research aims to determine the direct positive and significant influence of service on purchasing interest of Brio Honda buyers at the Honda Arista Ringroad Medan showroom, the direct positive and significant influence of price perception on buyers' purchasing interest, the direct positive and significant influence of emotional responses on purchasing interest, the influence of service on emotional responses through buying interest, the influence of price perception on emotional responses through buying interest and to find out the influence of service, price perception and emotional response on buying interest at the Honda Arista Ringroad Medan showroom. There is a positive influence of service on emotional responses at Brio Honda. At the Honda Arista Ringroad Medan Showroom, t-count 12,372 t-count 12,372>1,689. There is an influence of price perception on emotional responses at the Brio Honda at the Honda Arista Ringroad Medan Showroom, because the t-count of 11,176 is greater than the t-table of 1,689. There is a positive influence of service on buyer interest in Brio Honda at the Honda Arista Ringroad Medan Showroom, because the t count of 12,249 is greater than the t-table of 1,689. There is a positive influence of price perception on buyer interest in Brio Honda at the Honda Arista Ringroad Medan Showroom, because the t count of 1,937 is greater than the t-table of 1,689. There is a simultaneous positive influence of service and price perception on the emotional response at Brio Honda at the Honda Arista Ringroad Medan Showroom because the calculated F1 is greater than the F table (409,515> 4.121) and F2 (513,423> 4.121). The percentage of influence of the independent variable on the dependent based on the determinant test is 97.5%.